Classes granulométricas e modo de aplicação de calcário na cultura do milho - RATKE, Rafael Felippe (2011)
Lime particle size is key to soil correction as it defines the reactivity of the soil due to its low solubility. The lime presenting a particle size larger than 0,3 mm corrects soil acidity and enables soil residual effect whereas the finely ground lime presents a lower residual effect, however; it promotes soil acidity correction and can percolate in the layer correcting subsoil acidity. This study aimed at clarifying chemical alterations in the soil applying lime following two procedures: i)incorporation of limestone presenting particle size larger than 0.3 mm and; ii) finely ground limestone onto the soil surface. Both liming strategies were performed at corn crops harvested in 2008/2009 and 2009/2010. The experiments were assembled into randomized blocks with four repetitions using dystroferric Red Latosol. The incorporated dolomitic lime particle sizes were as follows: 0.20 mm to 0.30 mm; 0.30 mm to 0.56 mm; 0.56 mm to 0.82 mm and 0.82 mm to 2.00 mm, at doses of 1.3; 2.6; 3.9 e 6.5 t ha-1 respectively. The lime particle sizes applied onto soil surface were as follows: 0.30 mm to 0.20 mm; 0.20 mm to 0.10 mm; 0.10 mm to 0.05 mm and 0.05 mm to 0.01 mm, at the dose of 1.3 t ha-1, a control treatment (with no lime) was the same for both experiments. Chemical attributes of the soil, root attributes, leaf nutrients and corn yield were assessed at two crops 2008/2009 and 2009/2010. The results demonstrated that by using higher doses of lime with less reactive particle sizes, i.e., larger than 0.30 mm, it was possible to correct the soil in the same way as using lime with 0.20 mm to 0.30, and with residual effect on the second year of research. The use of lime with particles of 0.30 to 0.20 applied onto soil surface reduced exchangeable Al and increased the levels of Ca and Mg within the soil profile. The use of lime presenting particle size larger than 0.82 mm and at the quantity of 6.5 t ha-1 applied and incorporated onto the soil evidenced root lengthening of the corn at the layer of 20-40 cm of depth in the soil. There was higher corn yield on the first year using the same particle size. Regarding the second crop, there was no difference concerning corn yield among lime particle sizes incorporated to the soil. Corn yield was not influenced by the use of finely ground lime onto the soil at both assessed crops. The level of corn leaf nutrients were influenced by the use of lime of different particle sizes incorporated and superficially applied to the soil. The root lengthening at the layer of 20-40 cm of depth was greater when there was the use of lime particle sizes between 0.30 mm and 0.20 applied to soil surface. Root attributes assessed at corn crop with the use of lime with different particle sizes correlated with leaf levels of Cu on the first year, and of K and Ca on the second year. There was a correlation between the length of the roots and corn yield on the second year as well. The use of finely ground lime onto soil surface promoted a significant correlation between root mass and the level of Mn in the corn leaves on the first year.